Tingkat Kesukaan Konsumen Terhadap Jelly Drink Rumput Laut (Euchema cottonii) - Rahael, Kristhina P.; Sudirjo, Fien; Royani, D.S.; Marasabessy, I; Amahorseja, Anggeline (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
The use of seaweed in various industries is currently increasingly widespread. This makes the need for seaweed as a raw material increasingly increasing, apart from that the international market is also aggressively receiving seaweed from Indonesia. Southeast Maluku and the city of Tual have sufficient grass potential available. Nutmeg is a local fruit that is often found in the Maluku area. Kur District is one of the sub-districts of Tual City, which has quite abundant nutmeg plantations. So far, people only use mace and seeds, while the flesh is thrown away, even though the flesh is the largest component of nutmeg, namely 1:4. Jelly drink is a gel-shaped drink that is easy to suck, chewy and can be consumed as a hunger quencher. Gels can be formed through the mechanism of junction zone formation by hydrocolloids (such as carrageenan) together with sugar and acid. This drink has a viscosity level between fruit juice and jelly (Zega, 2010). Jelly drinks can be useful for improving digestion because this product contains fiber so it can also be categorized as a functional drink. Jelly drinks can be given additional ingredients containing vitamins to increase their nutritional value (Sudirjo and Ohoiwutun, 2015). The addition of nutmeg juice to jelly drinks has never been done. This research aims to determine the level of consumer acceptance of seaweed (E. cottonii) jelly drink with added nutmeg juice (Myristica fragrans Houtt). The research was conducted in December 2022 - January 2023, at the Fisheries Product Processing Laboratory, Tual State Fisheries Polytechnic. The ingredients used are dried E. cottonii seaweed and fresh nutmeg, as well as additional granulated sugar. The results showed that the addition of nutmeg juice with a concentration of 20% was preferred by the panelists, both in terms of appearance, color, texture, smell and taste parameters.